Regional Pro Bon Conference Held at Hilton Hotel - Watkins, Howard::::::::: (1989)
Fresno-Merced Counties Legal Services Executive Director Joe Romero speaking at lectern: seated: Frank D. Winston, State Senator Ken Maddy, Justice Hollis Best, Randi Saul-Olson and Glee Ewell Fresno-Merced Counties Legal Services=Fresno-Merced Counties Legal Services; as of 5/1/1989 Central California Legal Services